Trybunał jednoosobowy w kanonicznym prawie wschodnim - Przekop, Edmund (Prawo Kanoniczne, 1979)
The m otu proprio Sollicitudinem nostram (1950), treating th e adm in istratio n of justice in eastern ecclesiastical courts, in th e field of canonical procedure m any and im portant developm ents, valuable for any canonist in the E ast and in th e West, and it deserves th erefore closer investigation. It is not only th e law at present in force in the Catholics Churches E astern, but also, one dares to say, an excellent first draught of the fu tu re section De iudicis in a new L atin Code. This Eastern Code contains sections th a t are quite new, such as De compromisso in arbitros (cans. 98—122); De iudicio contentioso coram unico iudice (cans. 453—467), and others, especially cans. 544—567 on criminal trials. These innovations a re based on th e latest ideas on canonical procedure and will, doubtless, have a great im pact on this further development. The present article confines itself to th e canons on trials before a single judge in the Catholic Church Eastern. In th e first place, it notes some differences of collegiate and noncollegiate (single judge) tribunals. In the second place, th e re are explained th e new fundam ental principles on w hich th e section on th e single judge in the Eastern Code is based; and, finally, an indication is given of the sources of this section as a w hole and, as fa r as possible, of each canon in particular.